Ethical Conundrums in the Clinical Laboratory - Das, Saswati (Asian Journal of Medical Sciences, 2021)
Ethics guide in difficult situations to make the distinction between right and wrong. Professional ethics ought to be given priority in laboratory medicine. Laboratory results deeply impact the decisions of the physician and the well-being of the patient. Hence, the ethical dilemmas in the laboratory have to be addressed to achieve better care for the patient. Ethics encompasses all the three phases – pre analytical , analytical and post analytical of the total testing cycle. Practical implementation of ethical codes is always a challenge. In this paper we aim to decode the various ethical considerations that need to be addressed during the total testing cycle while working in a resource constrained settings and the ethical conundrums during a public health crisis.